Contraceptive use among adolescent and young women in North and South Kivu, Democratic Republic of the Congo: A cross-sectional population-based survey. - Sara E Casey; Meghan C Gallagher; Jessica Kakesa; Anushka Kalyanpur; Jean-Baptiste Muselemu; Raoza Vololona Rafanoharana; Nathaly Spilotros (PLoS Medicine, 2020)
Background Adolescent girls in humanitarian settings are especially vulnerable as their support systems are often disrupted. More than 20 years of violence in the Democratic Republic of the Congo (DRC) has weakened the health system, resulting in poor sexual and reproductive health (SRH) outcomes for women. Little evidence on adolescent contraceptive use in humanitarian settings is available. CARE, International Rescue Committee (IRC), and Save the Children, in collaboration with the Reproductive Health Access, Information and Services in Emergencies (RAISE) Initiative, Columbia University, have supported the Ministry of Health (MOH) since 2011 to provide good quality contraceptive services in public health facilities in conflict-affected North and South Kivu. In this study, we analyzed contraceptive use among sexually active young women aged 15-24 in the health zones served by the partners' programs. Methods and findings The partners conducted cross-sectional population-based surveys in program areas of North and South Kivu using two-stage cluster sampling in six health zones in July-August 2016 and 2017. Twenty-five clusters were selected in each health zone, 22 households in each cluster, and one woman of reproductive age (15-49 years) was randomly selected in each household. This manuscript presents results from a secondary data analysis for 1,022 women aged 15-24 who reported ever having sex: 326 adolescents (15-19 years) and 696 young women (20-24 years), 31.7% (95% confidence interval [CI] 29.5-34.1), of whom were displaced at least once in the previous five years. Contraceptive knowledge was high, with over 90% of both groups able to name at least one modern contraceptive method. Despite this high knowledge, unmet need for contraception was also high: 31.7% (95%CI 27.9-35.7) among 15-19-year-olds and 40.1% (95% CI 37.1-43.1, p = 0.001) among 20-24-year-olds. Current modern contraceptive use (16.5%, 95% CI 14.7-18.4) was similar in both age groups, the majority of whom received their method from a supported health facility. Among current users, more than half of 15-19-year-olds were using a long-acting reversible contraceptive (LARC; 51.7%, 95% CI 41.1-61.9) compared to 36.5% of 20-24-year-olds (95% CI 29.6-43.9, p = 0.02). Age, younger age of sexual debut, having some secondary education, being unmarried, and having begun childbearing were associated with modern contraceptive use. The main limitations of our study are related to insecurity in three health zones that prevented access to some villages, reducing the representativeness of our data, and our defining sexually active women as those who have ever had sex. Conclusions In this study, to our knowledge one of the first to measure contraceptive prevalence among adolescents in a humanitarian setting, we observed that adolescent and young women will use modern contraception, including long-acting methods. Meaningful engagement of adolescent and young women would likely contribute to even better outcomes. Creating an enabling environment by addressing gender and social norms, however, is key to reducing stigma and meeting the demand for contraception of young women. As we continue to build such supportive environments, we can see that they will use effective contraception when contraceptive services, including short- and long-acting methods, are available, even in protracted crisis settings.